Effect of catalysts on the conversion of polystyrene plastic waste into fuel with the Catalytic Cracking Method - Daniar, Rima; Kholidah, Nurul (ALKIMIA, 2020)
Polystyrene is useful product that widely used today. But when it becomes waste, Polystyrene can cause environmental problem such as air pollution, soil contamination, as well as economical resistence due to the increase of space and disposal costs. On the other hand Polystyrene can be converted into fuel. It is expected can be a solution of the problem. The aim of this research is to convert polystyrene plastic waste into useful fuel with catalytic cracking process. Zeolit and Al2O3 was used as catalyst in this research as musch as 8 % feed. Temperature set at 250 oC. At the optimum reaction condition (catalyst Al2O3 and the length of cracking time is 30 minutes) the liquid yield of catalytic cracking process was 29.40 %. Physical properties like density, spgr, oAPI gravity and calorific value of fuel samples is determined and compared to gasoline standard. The result showed that density, spgr, oAPI gravity and calorific value was close to the density, spgr, oAPI gravity and calorific value of gasoline standard.